Proceedings of the 5th China Aeronautical Science and Technology Conference - SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
To sort out the progress of aviation science and technology and industry, look forward to the future development trend, commend scientific and technological innovation achievements and talents, strengthen international cooperation, promote discipline exchanges, encourage scientific and technological innovation, and promote the development of aviation, the Chinese Aeronautical Society holds a China Aviation Science and Technology Conference every two years, which has been successfully held for four times and has become the highest level, largest scale, most influential and authoritative science and technology conference in the field of aviation in China. The 5th China Aviation Science and Technology Conference will be held in Wuzhen, Jiaxing City, Zhejiang Province in 2021, with the theme of "New Generation of Aviation Equipment and Technology", with academician Zhang Yanzhong as the chairman of the conference. This book contains original, peer-reviewed research papers from the conference. The topics covered include but are not limited to navigation, guidance and control technologies, key technologies for aircraft design and overall optimization, aviation test technologies, aviation airborne systems, electromechanical technologies, structural design, aerodynamics and flight mechanics, other related technologies, advanced aviation materials and manufacturing technologies, advanced aviation propulsion technologies, and civil aviation transportation. The papers presented here share the latest discoveries on aviation science and technology, making the book a valuable asset for researchers, engineers, and students.
Keywords: Aerospace engineering; Astronautics; Control engineering; Robotics; Automation; Aerospace Technology and Astronautics; Control, Robotics, Automation; Aeronautics -- Congresses; Aerospace engineering -- Congresses